Sistema tecnológico y su incidencia en la gestión económica financiera de la agencia de BanEcuador El Empalme, año 2022 - Villarreal Vera, Laura Angélica (2023)
The purpose of this research, title "Technological system and its impact on the economic financial management of the BanEcuador banking entity from canton El Empalme, year 2022," was to evaluate the impact of the technological system on the economic financial management of the BanEcuador banking entity from canton El Empalme in 2022.The elaboration of the present investigation whose theme is "Technological system and its incidence in the financial economic management of the BanEcuador El Empalme agency, year 2022", had as a general objective to evaluate the incidence of the technological system in the financial economic management of the Agency of BanEcuador El Empalme, year 2022. As part of its methodology, explanatory, descriptive, sectional, and case study research was used, additionally, the analytical, deductive and inductive method was used, to clearly expose the exhaustive research carried out on the incidence of the technological system in the financial economic management of the Agency of BanEcuador EP El Empalme, year 2022. An interview questionnaire was applied to the Manager of BanEcuador EP agency El Empalme, and a survey questionnaire was applied to a selected sample of clients of the same institution, in order to get their opinions on the problem raised. The results obtained show that this institution only has a web page to be able to provide some digital services to its clients, and it does not have its own ATMs, with a Mobile App and they do not offer the service of non-banking correspondents to their clients as other banking entities that operate in the El Empalme canton do. It is concluded that due to weak management, it has not been possible to execute 100% of the 8 initiatives implemented in the POA of BanEcuador EP since 2021, therefore the few technological services that are currently being provided in the banking agency, cover half the expectations of its customers. Therefore, the incidence of technological services is relatively low in the financial management of the BanEcuador agency in the El Empalme canton, due to the fact that technological services have not been implemented or strengthened in 2022, but despite this, Customer acceptance and demand for existing services was considerably good in the same year. It is recommended that you implement new services and functionalities that allow your customers to manage all their banking transactions in an agile and efficient manner. As part of its methodology, we used the explanatory, descriptive, sectional, and case study research. Additionally, the analytical, deductive, and inductive methods were applied to carry out the exhaustive research about the topic. An interview questionnaire was applied to the Manager of the BanEcuador banking entity from canton El Empalme, and a survey questionnaire was given to a selected group of customers from the same institution to know their opinions about the problem raised. The results obtained indicate that the institution has a website to provide some digital services to its customers, and it does not have its own ATMs or a mobile application. Furthermore, it does not offer non-bank correspondent services to its clients like other banking entities that operate in the El Empalme canton. Due to the limited technological services offered by BanEcuador banking entity from canton El Empalme, 8 planned initiatives in their 2021 POA could not be fully executed. Therefore, the impact of technological services is relatively low in the financial management of the banking entity. Although new technological services have not been implemented or strengthened in 2022, the acceptance and demand for the existing services were considerably good in the same year. It is recommended to implement new services and functionalities that allow their clients to manage all their banking transactions in an agile and efficient way. The elaboration of the present investigation whose theme is "Technological system and its incidence in the financial economic management of the BanEcuador El Empalme agency, year 2022", had as a general objective to evaluate the incidence of the technological system in the financial economic management of the Agency of BanEcuador El Empalme, year 2022. As part of its methodology, explanatory, descriptive, sectional, and case study research was used, additionally, the analytical, deductive and inductive method was used, to clearly expose the exhaustive research carried out on the incidence of the technological system in the financial economic management of the Agency of BanEcuador EP El Empalme, year 2022. An interview questionnaire was applied to the Manager of BanEcuador EP agency El Empalme, and a survey questionnaire was applied to a selected sample of clients of the same institution, in order to get their opinions on the problem raised. The results obtained show that this institution only has a web page to be able to provide some digital services to its clients, and it does not have its own ATMs, with a Mobile App and they do not offer the service of non-banking correspondents to their clients as other banking entities that operate in the El Empalme canton do. It is concluded that until now, due to poor management, 8 initiatives implemented in the POA of BanEcuador EP since 2021 have not been able to be 100% executed. It is recommended that new services and functionalities be implemented that allow its clients to manage all their transactions. banks in an agile and efficient way.